Effects of ultrasonic scaling and hand-activated scaling on tactile sensitivity in dental hygiene students. - Ryan DL; Darby M; Bauman D; Tolle SL; Naik D (Journal of Dental Hygiene)
Purpose. This study was conducted to determine if tactile sensitivity varies in dental hygiene students who use the ultrasonic scaler, as compared to those who scale with hand-activated instruments.Methods. A two-group, randomized subjects, pretest-posttest design was carried out mid-semester for five weeks on 40 first-year dental hygiene students who met the inclusion criteria of this study and who agreed to participate. A convenience sample of 40 consenting, first-year dental hygiene students were randomly assigned to one of two groups (experimental or control). After establishing a baseline tactile sensitivity score with the Vibratory Sensory Analyzer (VSA), experimental group subjects used the ultrasonic scaler to remove 4cc's of artificial calculus from a typodont in a controlled, simulated clinical setting for 45 minutes, while each control subject manually scaled 4cc's of artificial calculus on a typodont in a controlled, simulated situation for 45 minutes. Immediately following exposure to either the ultrasonic scaler or hand-activated scaling instruments, tactile sensitivity scores were obtained using the VSA. Analysis of variance with one repeated measures factor was used to determine between group and within group differences on the pretest and posttest tactile sensitivity scores.Results. Results revealed that tactile sensitivity increased after a 45-minute scaling session with the ultrasonic scaler. Pretest to posttest changes in tactile sensitivity for the ultrasonic scaling group exhibited a much larger threshold as compared to those in the hand-activated scaling group, supporting a gain in students' level of sensitivity with stimulus (vibration). Tactile sensitivity decreased in those who used hand-activated scaling instruments. The thumb, index, and middle fingers of students in both groups showed similarities in tactile sensitivity, with the index finger being the most sensitive.Conclusion. Tactile sensitivity decreases with hand-activated scaling and increases with ultrasonic scaling over a 45-minute period. Short-term vibration exposure from the ultrasonic scaler is insufficient to negatively affect tactile sensitivity.